2014
DOI: 10.1515/cclm-2014-0165
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated platelets: analytical aspects and clinical utility

Abstract: Reticulated platelets are immature platelets circulating in blood; they reflect the activity of megakaryopoiesis in the bone marrow. Therefore, they can be used as a non-invasive test in patients with thrombocytopenia in various clinical conditions. The preferred method of analysis is by flow cytometry. However, there is an evident lack of analytical standardization, making it difficult to compare results obtained in different laboratories. Currently, two types of hematology analyzers are on the market offerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
147
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 83 publications
3
147
1
6
Order By: Relevance
“…Many studies showed that RP measurement is a non-invasive test that represents a surrogate marker for megakaryocytic activity [13][14][15][16][17][18][19][20][21] . Therefore, the current study aimed to evaluate the RP% in patients with chronic hepatitis C as an index of platelet production and to evaluate the relationship between the RP% and the platelet count in those patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies showed that RP measurement is a non-invasive test that represents a surrogate marker for megakaryocytic activity [13][14][15][16][17][18][19][20][21] . Therefore, the current study aimed to evaluate the RP% in patients with chronic hepatitis C as an index of platelet production and to evaluate the relationship between the RP% and the platelet count in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…The RP contain residual messenger RNA (mRNA), they are functionally active and are equivalent to the reticulocytes of erythropoiesis. The RP are non-invasive indicator of recent megakaryopoiesis in the bone marrow, therefore, may be used to determine whether thrombocytopenia is due to decreased production or peripheral destruction of platelets [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be increased in idiopathic thrombocytopenic purpura and myeloproliferative disorder, and decreased in aplastic anaemia [9,10]. In addition, there were reports that PDW Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores descrevem o teste, como avaliação da cinética plaquetária. (Abe et al, 2005;Jiménez et al, 2006;Kajihara et al, 2007;Kile, 2009;Hoffmann, 2014 Horstman, 2002;Gernsheimer, 2008;Tantawy et al, 2010).…”
Section: Introductionunclassified